2016
DOI: 10.1074/jbc.r115.709444
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Minireview Series on Modern Technologies for In-cell Biochemistry

Abstract: The last decade has seen enormous progress in the exploration and understanding of the behavior of molecules in their natural cellular environments at increasingly high spatial and temporal resolution. Advances in microscopy and the development of new fluorescent reagents as well as genetic editing techniques have enabled quantitative analysis of protein interactions, intracellular trafficking, metabolic changes, and signaling. Modern biochemistry now faces new and exciting challenges. Can traditionally "in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Tumor-derived organoids can mimic all the typical characteristics of the initial tumor mass, the three-dimensional (3D) structural framework and the property for uncontrolled growth. It has therefore been shown that organoids can not only recapitulate the genetic modifications that arise in cancer cells with high fidelity ( 98 ), but can also provide unique opportunities for the generation of fully characterized models at an unprecedented rate.…”
Section: Organoids: Smart Weapons Against Complex Genetic Diseasesmentioning
confidence: 99%
“…Tumor-derived organoids can mimic all the typical characteristics of the initial tumor mass, the three-dimensional (3D) structural framework and the property for uncontrolled growth. It has therefore been shown that organoids can not only recapitulate the genetic modifications that arise in cancer cells with high fidelity ( 98 ), but can also provide unique opportunities for the generation of fully characterized models at an unprecedented rate.…”
Section: Organoids: Smart Weapons Against Complex Genetic Diseasesmentioning
confidence: 99%
“…The CRISPR/Cas9 system also enables researchers to implement gene modifications in vitro , which are hard to accomplish directly in a human body ( Guye et al, 2016 ). Therefore, wild-type or disease-causing genes along with their downstream effects can be analyzed in a more rapid and reliable manner, and the off-target effects manifest themselves less after correction of genes in an organoid ( Lutsenko, 2016 ). Genetically modified organoids have been successfully transplanted into a damaged colon for tissue repair and function recovery.…”
Section: A Summary and Future Directionsmentioning
confidence: 99%
“…Especially for chronic inflammation, new models are necessary to obtain more direct and convincing evidence for more detailed research into the role of chronic inflammation in carcinogenesis ( Watson et al, 2014 ; Wiener et al, 2014 ; Sinagoga and Wells, 2015 ). Infectious organoids can also be genetically manipulated to study genes and epigenetic factors in the development of inflammation ( Fujii et al, 2015 ; Lutsenko, 2016 ). The CRISPR/Cas9-mediated correction has been successfully applied to the CFTR mutation for the treatment of patients with CF ( Durand et al, 2012 ; Liu et al, 2012 ; Schwank et al, 2013 ; Martin, 2015 ; Mou et al, 2015 ; Dedhia et al, 2016 ).…”
Section: A Summary and Future Directionsmentioning
confidence: 99%